A Critique on the Book "The Meaning of Icons" - Nahid Abdi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Perceiving the principles of Christian arts as one of the monotheistic religions has a special significance in the studies of thought and art. In spite of the explicit prohibition of the Abrahamic religions on Image, it is important to know how icons and iconography have become essential elements of Christianity. It was expected that this book could respond part of this expectation. This article discussed some of the positive points and shortcomings of the two texts from the point of critical studies method. Thus, it was noted that the translation with manipulating the framework of the source has affected the goals of the book; meanwhile, because of the lack of proper approach, questions on “The Meaning of Icons” have been remained unresolved yet. The lack of a bibliography is a fundamental shortcoming of the Persian version, and the failure to follow the standards of research has subjected the validity and effectiveness of the book. Because of the deficiencies and mixing the content, the present translation does not seem to answer the needs of readers who have interested in this field and cannot be considered as a reliable text.